Radiation measurements at the German antarctic Neumayer Station ... - Wuttke, Sigrid; Seckmeyer, Gunther; Schrems, Otto; König-Langlo, Gert (Bellingham Wash. : SPIE, 2005)
During the austral summer 2003/04 the Institute for Meteorology and Climatology, University of Hannover, Germany, has deployed a newly developed spectroradiometric system at the permanent German Antarctic Neumayer Station (70° 39' S, 8° 15' W). Aim of this campaign was to characterize the solar radiation conditions in an Antarctic environment. These are different from other areas of the Earth due to extremely high reflection of the ground (albedo). Relatively low cloud optical depths and ozone depletion further contribute to rather different radiation conditions compared to mid-latitudes. The investigation of these conditions will improve the understanding of the impact of climate change and ozone depletion in polar regions. Spectral irradiance and radiance as well as luminance and spectral albedo have been measured in a wavelength range from 280 to 1050 nm. With this set of radiation parameters it is assured that directional information of incident radiation parameters as well as the impact of surface ...